Electric document delivery: the Ibadan University Library experience (2011)
New information communication technologies, such as the internet and electronic publishing, not ony enhance the range of publications that libraries can provide for their users but also increase the speed with which such requests can be met. This article describes the development of electronic document delivery(EDD) at the Kenneth Dike Library at the University of Ibadan, Nigeria. A successful EDD program depends upon good intranet and internet network systems, document availability, user awareness and training, and ease of use. The major challenge to this service is inconsistent power supply which the university is addressing with the aid of a grant from the MacArthur Foundation for backup electric generator and a university solar energy project. It is hoped that this will assure better and more reliable power service in support of EDD in future. New information delivery regulations and laws guiding adequate service will also emerge but must be properly applied for effective and positive results.